2019
DOI: 10.1038/s41419-019-1985-3
|View full text |Cite
|
Sign up to set email alerts
|

Phlpp1 is associated with human intervertebral disc degeneration and its deficiency promotes healing after needle puncture injury in mice

Abstract: Back pain is a leading cause of global disability and is strongly associated with intervertebral disc (IVD) degeneration (IDD). Hallmarks of IDD include progressive cell loss and matrix degradation. The Akt signaling pathway regulates cellularity and matrix production in IVDs and its inactivation is known to contribute to a catabolic shift and increased cell loss via apoptosis. The PH domain leucine-rich repeat protein phosphatase (Phlpp1) directly regulates Akt signaling and therefore may play a role in regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 60 publications
2
23
0
Order By: Relevance
“…Further enhancement of cell proliferation as a result of Phlpp1 inhibition has potential implications beyond chondrocytes. Phlpp1 deletion promotes cell proliferation in a model of intervertebral disc degeneration, (19 ) and regulation of cell apoptosis by Phlpp1 is implicated in ischemic brain and spinal cord injury, ( 20,22 ) colitis, ( 21 ) cardiac dysfunction, ( 66 ) pancreatic beta‐cell survival, ( 67 ) and tumor activity. ( 8 ) As such, enhancement of signals associated with Phlpp1 inhibition could have a profound impact on various physiological and disease processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further enhancement of cell proliferation as a result of Phlpp1 inhibition has potential implications beyond chondrocytes. Phlpp1 deletion promotes cell proliferation in a model of intervertebral disc degeneration, (19 ) and regulation of cell apoptosis by Phlpp1 is implicated in ischemic brain and spinal cord injury, ( 20,22 ) colitis, ( 21 ) cardiac dysfunction, ( 66 ) pancreatic beta‐cell survival, ( 67 ) and tumor activity. ( 8 ) As such, enhancement of signals associated with Phlpp1 inhibition could have a profound impact on various physiological and disease processes.…”
Section: Discussionmentioning
confidence: 99%
“…( 12 ) Phlpp1/2 have been implicated as tumor suppressors, ( 9,13,14 ) but also regulate metabolic processes, ( 15 ) inflammation, ( 16 ) and tissue regeneration following injury. ( 17–24 ) Phlpp1 is overexpressed in human osteoarthritic tissue and Phlpp1 inactivation improves murine posttraumatic osteoarthritis. ( 17 ) Phlpp1 deletion accelerates chondrocyte maturation in vitro, preserves articular cartilage in vivo, and increases mobility in mice with posttraumatic osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%
“…These changes were consistent with the previous studies showing loss of proteoglycans and less organized collagens during the initial phase of disc degeneration. 29 31 …”
Section: Discussionmentioning
confidence: 99%
“…PHLPP1-KO mice develop normally with no anatomical defects, consistent with previously reported studies showing that PHLPP1-KO mice are viable and show no overt changes in growth, anatomy, or development ( Chen et al, 2013 ; Masubuchi et al, 2010 ). In addition, mice with systemic deletion/inhibition of PHLPP1 show promising neuro-, cardio-, and intestine-protection as well as tissue regeneration in several pathological settings ( Chen et al, 2013 ; Hwang et al, 2018 ; Jackson et al, 2018 ; Moc et al, 2015 ; Wen et al, 2015 ; Zhang et al, 2019 , 2020 ). In our long-term mouse studies, no tumorigenic features were observed in PHLPP1-KO mice; they live to a relatively old age without development of tumors.…”
Section: Discussionmentioning
confidence: 99%